Power-curriculum, collective memory, and alternative approaches in learning history - Kurniawan, Ganda Febri (Jurnal Teori dan Praksis Pembelajaran IPS, 2023)
This study analyzes the curriculum's influence, collective memory formation, and alternative approaches to learning history. This research was carried out using qualitative methods with a descriptive approach. The data in this study consisted of 3 sources: informants, documents, and learning activities. Data analysis applied Critical Discourse Analysis (CDA). The research findings show that, as a reference document, the curriculum also has a negative impact on teachers, one of which is the perception that the curriculum is a rigid document and inhibits teacher freedom. So that in learning history, collective memory is formed based on official history, which is very difficult for teachers to provide information about alternative history. Teachers must implement alternative learning approaches such as humanism, critical pedagogy, and reflective approaches. To create a more enjoyable learning atmosphere and to accommodate all groups in Indonesia to be involved in discussing the history of their nation, which is humane and free from grudges and hatred.